3D Bended Metasurfaces: Asymmetrical Chirality in 3D Bended Metasurface (Adv. Funct. Mater. 31/2021). (4th August 2021) - Pan, Ruhao; Liu, Zhe; Zhu, Wei; Du, Shuo; Gu, Changzhi; Li, Junjie
Abstract : In article number 2100689, Changzhi Gu, Junjie Li, and co‐workers successfully fabricate a 3D bended metasurface with arrays of asymmetric split ring resonators using focused ion beam‐defined origami. Both giant circular dichroism (CD) and asymmetric chirality properties are realized simultaneously in the same metasurface, and the CD for the forward and backward incidence at mid‐infrared range are −0.29 and 0.71, respectively.